Laparoscopic management of ruptured non communicating rudimentary horn in second trimester of pregnancy - Jha, Akriti; Gupta, Richa; Gupta, Lavesh; Gupta, Deepesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Rudimentary horn is a developmental anomaly of the uterus. Pregnancy in rudimentary horn is rare occurrence with incidence of less than 1 in 150,000. Prerupture diagnosis of rudimentary horn pregnancy with USG is technically difficult, with sensitivity of 30%. It is often not diagnosed unless it terminates by rupture in the second trimester leading to catastrophic haemorrhage and hence high incidence of maternal mortality. Management of such cases is a challenge till today due to diagnostic dilemma. Expertise in ultrasonography and early resort to surgical management is life saving in such cases. Here we present a case of ruptured non-communicating rudimentary horn pregnancy at 15 weeks presenting in our emergency department as a case of pain abdomen. Laparoscopic resection of the rudimentary horn was performed for the patient.